2018
DOI: 10.1093/nar/gky1109
|View full text |Cite
|
Sign up to set email alerts
|

RNA polymerase III subunits C37/53 modulate rU:dA hybrid 3′ end dynamics during transcription termination

Abstract: RNA polymerase (RNAP) III synthesizes tRNAs and other transcripts, and mutations to its subunits cause human disorders. The RNAP III subunit-heterodimer C37/53 functions in initiation, elongation and in termination-associated reinitiation with subunit C11. C37/53 is related to heterodimers associated with RNAPs I and II, and C11 is related to TFIIS and Rpa12.2, the active site RNA 3′ cleavage factors for RNAPs II and I. Critical to termination is stability of the RNA:DNA hybrid bound in the active center, whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 60 publications
2
20
0
Order By: Relevance
“…RNAP3 is predominantly implicated in the transcription of the short and abundant tRNA and 5S rRNA species. In vitro transcription assays have indicated that once loaded, RNAP3 can terminate transcription autonomously upon reaching a transcription termination signal, which is constituted by a simple stretch of five thymine residues on the non-template strand (Mishra & Maraia, 2019), although this number may vary for different genes and organisms (reviewed in Arimbasseri et al 2013). TFIIIB in turn recruits the 17 subunits of RNAP3 complex at the TSS to initiate transcription (reviewed in Schramm and Hernandez 2002).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…RNAP3 is predominantly implicated in the transcription of the short and abundant tRNA and 5S rRNA species. In vitro transcription assays have indicated that once loaded, RNAP3 can terminate transcription autonomously upon reaching a transcription termination signal, which is constituted by a simple stretch of five thymine residues on the non-template strand (Mishra & Maraia, 2019), although this number may vary for different genes and organisms (reviewed in Arimbasseri et al 2013). TFIIIB in turn recruits the 17 subunits of RNAP3 complex at the TSS to initiate transcription (reviewed in Schramm and Hernandez 2002).…”
Section: Introductionmentioning
confidence: 99%
“…In fission yeast, an upstream TATA box assists TFIIIC in recruiting TFIIIB and is essential for the proper recruitment of RNAP3 (Hamada et al, 2001). In vitro transcription assays have indicated that once loaded, RNAP3 can terminate transcription autonomously upon reaching a transcription termination signal, which is constituted by a simple stretch of five thymine residues on the non-template strand (Mishra & Maraia, 2019), although this number may vary for different genes and organisms (reviewed in Arimbasseri et al 2013). The C37/53/11 subcomplex of RNAP3 is particularly important for this intrinsic transcription termination mechanism (Arimbasseri et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Instead, the low GC content of the genomic regions from which these RNA species arise inherently causes RNAPII to be termination prone. Indeed, high AT content increases RNAPII pausing and backtracking 29 , and promotes termination by other RNA polymerases [30][31][32] , since AT-rich RNA-DNA hybrids destabilize the ternary elongation complex. In addition, AT-rich RNAs fail to form stable secondary structures that prevent RNAPII backtracking and arrest 33,34 .…”
Section: Effect Of the Transcribed Sequence Is Independent Of Contextmentioning
confidence: 99%
“…2b, Supplementary Video 1). Multiple studies reported that Pol III requires RPC10 (C11 in yeast) to terminate transcription, but that its 3' RNA cleavage activity is not essential for this process 9,11,12,27,28 . We propose that the insertion of RPC10 C-ribbon induces partial opening of the mobile clamp domain and, thereby, supports the release of transcribed RNA from a paused pre-termination complex previously reported 10 .…”
Section: Rpc10 Swings Into the Active Sitementioning
confidence: 99%